Aluminum nitride substrate with low edge crack angle rate and method for manufacturing the same

CN121698659BActive Publication Date: 2026-10-27JIANGSU BREE OPTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511775514.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-10-27
Estimated Expiration
2045-11-28

AI Technical Summary

Technical Problem

但是,氮气气流分布不均匀会直接引起炉内热场分布不均,使得基板在烧结过程中承受不均匀的热应力,进而产生裂边、裂角等缺陷,严重影响产品成品率和可靠性

Benefits of technology

[0020]在上述技术方案中,通过控制刮刀间隙在0.3~1.2 mm范围内,配合5~8 cm/min的流延速度,能够精确控制浆料的铺展厚度和均匀性,同时采用60~80 ℃的干燥温度和30~60min的干燥时间,可确保混合溶剂中的乙醇和丙酮匀速挥发而不引起坯体开裂或变形,最终获得厚度为0.25~1.1mm、密度≥2.4 g/cm3的生坯,这种高密度且结构均匀的生坯为后续排胶、烧结环节的顺利进行奠定了良好基础,有效避免了因生坯结构缺陷导致的烧结裂边裂角问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121698659B_ABST
    Figure CN121698659B_ABST
Patent Text Reader

Abstract

The application discloses an aluminum nitride substrate with low edge crack and corner crack rate and a preparation method thereof, and belongs to the technical field of aluminum nitride substrate preparation. The preparation method of the aluminum nitride substrate comprises the following steps: mixing aluminum nitride powder and composite sintering aids in proportion to prepare a casting slurry, obtaining a green body through casting forming, and placing the green body into a calcining furnace for sintering after glue removal treatment, wherein a perforated plate airflow screen is arranged at an air inlet of a furnace chamber, and nitrogen flow, flow rate and pressure are regulated in stages. The preparation method of the application greatly reduces the edge crack and corner crack rate of the substrate on the basis of improving the performance index of the substrate. The prepared aluminum nitride substrate has the characteristics of high thermal conductivity, high density and low edge crack and corner crack rate, and meets the demand of the electronic manufacturing field such as high-temperature electronic devices and high-power module packaging for high-performance aluminum nitride substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of aluminum nitride substrate preparation technology, and in particular to an aluminum nitride substrate with low crack edge ratio and its preparation method. Background Technology

[0002] With the miniaturization, high performance, and high power of electronic devices, stringent requirements are being placed on the heat dissipation, mechanical properties, and stability of electronic packaging materials. Aluminum nitride (ANT) substrates, due to their excellent overall performance, are widely used in large-scale integrated circuits, automotive electronics, aerospace, and other fields. However, ANT substrates commonly suffer from edge and corner cracking during sintering, severely impacting product quality and yield. While attempts to improve this through formula optimization, molding processes, or sintering parameter control have yielded limited results and often increase costs or process complexity, nitrogen gas is typically introduced into the calcination furnace as a protective atmosphere to ensure sintering quality. However, uneven nitrogen gas flow distribution directly leads to uneven thermal field distribution within the furnace, causing the substrate to experience uneven thermal stress during sintering, resulting in defects such as edge and corner cracking, severely affecting product yield and reliability. Therefore, developing a preparation method that can effectively reduce the edge and corner cracking rate of ANT substrates has become an urgent technical problem to be solved in this field. Summary of the Invention

[0003] This application provides an aluminum nitride substrate with low edge cracking and a method for its preparation. The preparation method optimizes the raw material composition ratio and implements precise control of nitrogen gas flow in the calcination furnace. While improving the substrate performance indicators, it significantly reduces the edge cracking and aperture ratio of the substrate, effectively improving the sintering quality and product yield of the aluminum nitride substrate. The resulting aluminum nitride substrate has the characteristics of high thermal conductivity, high density and low edge cracking and aperture ratio, meeting the demand for high-performance aluminum nitride substrates in the electronic manufacturing fields such as high-temperature electronic devices and high-power module packaging.

[0004] In a first aspect, embodiments of this application provide an aluminum nitride substrate with low cracking edge and cracking angle ratio. The substrate composition, by mass parts, includes: 94-97 parts of aluminum nitride powder, 1.5-3 parts of Y2O3, 0.5-2 parts of ZrO2, and 0.1-0.3 parts of CaF2; the purity of the aluminum nitride powder is ≥99.5%, and the particle size is 1-5 μm.

[0005] In the aforementioned technical solution, the inventors discovered that using high-purity aluminum nitride powder with a purity ≥99.5% and a particle size of 1~5μm as the matrix material, combined with a specific ratio of Y2O3, ZrO2, and CaF2 composite sintering aids, enables the components to produce a synergistic effect during the sintering process. Specifically, Y2O3 reacts with the alumina on the surface of the aluminum nitride powder at high temperatures to form a low-melting-point liquid phase, promoting sintering densification; ZrO2 effectively absorbs stress concentration during sintering through the volume effect generated by phase transformation, improving the fracture toughness of the matrix; while CaF2 forms gas phase transport channels at high temperatures, eliminating closed-pore structures and further enhancing the density of the matrix. This formulation design allows the substrate to achieve high density and high thermal conductivity while effectively releasing internal stress, ultimately significantly reducing the cracking rate of the substrate.

[0006] In some embodiments, the composition of the substrate, by mass, includes: 95-97 parts of aluminum nitride powder, 2-3 parts of Y2O3, 1-2 parts of ZrO2, and 0.2-0.3 parts of CaF2.

[0007] In the above technical solution, aluminum nitride powder serves as the core matrix material of the substrate, providing high thermal conductivity, excellent insulation, and basic mechanical strength, forming the skeleton of the substrate. Y₂O₃ is the main sintering aid, which can lower the sintering temperature, promote the sintering bonding between aluminum nitride particles, reduce internal porosity of the substrate, and improve density. ZrO₂, as an auxiliary sintering aid, works synergistically with Y₂O₃ to further optimize the sintering effect, while enhancing the thermal stability and thermal shock resistance of the substrate. Simultaneously, trace amounts of CaF₂ are added as an auxiliary agent to reduce the viscosity of the liquid phase during sintering, accelerate the diffusion of various components, refine the microstructure, and improve the thermal conductivity of the substrate.

[0008] In some embodiments, the aluminum nitride substrate satisfies at least one of the following conditions: (1) Density ≥ 3.25 g / cm³ 3 ; (2) Thermal conductivity ≥ 170 W / (m K); (3) The cracking ratio of the edge and the cracking angle is ≤1.2%.

[0009] In the above technical solution, the substrate structure can be densified, and the thermal conductivity and mechanical integrity can be improved simultaneously through the synergistic effect of each component. The high density ensures excellent structural support, the high thermal conductivity ensures efficient heat dissipation, and the extremely low cracking angle directly reflects that the internal stress is effectively controlled. The three factors work together to enable the resulting aluminum nitride substrate to meet the stringent requirements of high-power electronic devices for heat dissipation performance and reliability.

[0010] Secondly, embodiments of this application provide a method for preparing an aluminum nitride substrate with low crack edge and crack angle ratio, comprising the following steps: weighing the following raw materials by mass: 94-97 parts of aluminum nitride powder, 1.5-3 parts of Y2O3, 0.5-2 parts of ZrO2, and 0.1-0.3 parts of CaF2, and processing them into a pre-sintered green blank; placing the pre-sintered green blank in a calcining furnace, and obtaining an aluminum nitride substrate through a sintering process and post-treatment; wherein, an airflow screen is provided at the furnace inlet of the calcining furnace; nitrogen gas is introduced into the furnace through the airflow screen; the sintering process includes a heating stage, a holding stage, and a cooling stage; in the heating stage, the nitrogen gas flow rate is 30-50 L / min, the flow velocity is 0.5-0.8 m / s, and the pressure is 0.03-0.1 MPa; in the holding stage, the nitrogen gas flow rate is 20-40 L / min. The flow rate is 0.1~0.3 m / s, and the pressure is 0.08~0.1 MPa. During the cooling stage, the nitrogen flow rate is 60~80 L / min, the flow rate is 0.8~1.0 m / s, and the pressure is 0.1~0.15 MPa.

[0011] In the above technical solution, by precisely controlling the ratio of aluminum nitride powder to sintering aids Y2O3, ZrO2, and CaF2, it is possible to effectively promote the densification of the green body during sintering, improve the mechanical strength and thermal conductivity of the aluminum nitride substrate, and optimize the substrate microstructure through the synergistic effect of the various sintering aids. Simultaneously, the airflow screen at the furnace inlet ensures that nitrogen gas entering the furnace vertically is evenly dispersed, avoiding uneven temperature distribution in localized areas of the furnace caused by direct airflow, which could lead to substrate heating or compositional deviations. Furthermore, by combining precise control of nitrogen parameters in stages, the higher nitrogen flow rate, velocity, and pressure during the heating stage can quickly remove air from the furnace, forming a pure nitrogen protective atmosphere, while ensuring uniform heating of the substrate and avoiding stress concentration caused by local overheating. During the holding stage, a lower nitrogen flow rate and velocity are used to maintain the stability of the temperature and atmosphere in the furnace, promoting full sintering of the substrate. During the cooling stage, a large flow rate and high velocity of nitrogen can accelerate the dissipation of heat in the furnace, allowing the substrate to cool rapidly and reducing the generation of thermal stress. This significantly reduces internal stress concentration caused by temperature gradients and uneven atmosphere, ultimately resulting in aluminum nitride substrates that achieve excellent density and thermal conductivity while significantly reducing the cracking rate of the aluminum nitride substrate.

[0012] In some embodiments, the airflow screen is a perforated plate airflow screen, which is provided with vents that satisfy at least one of the following conditions: (1) The diameter of the vent hole is 1 mm to 3 mm; (2) The distribution density of the vent holes is 20 per 10 cm. 2 ~50 pieces / 10cm 2 .

[0013] In the above technical solution, the ventilation holes of the perforated plate airflow screen, with their specific aperture and distribution density, can decompose the single nitrogen gas flow entering the furnace into a large number of uniformly distributed micro-flows, forming a stable diffused air intake mode. This effectively eliminates the local airflow dead zones and eddy phenomena caused by traditional direct-blowing air intake, ensuring that the nitrogen atmosphere is uniformly distributed across the cross-section of the furnace. This provides a consistent temperature environment and sintering conditions for all parts of the substrate, thereby further reducing the temperature gradient and thermal stress concentration caused by local atmosphere differences, significantly improving the uniformity and consistency of substrate sintering, and reducing the risk of edge and corner cracking during the sintering process.

[0014] In some embodiments, the sintering process satisfies at least one of the following conditions: (1) During the heating stage, the nitrogen flow rate is 35~45 L / min, the flow velocity is 0.6~0.8 m / s, and the pressure is 0.05~0.08 MPa; (2) During the heat preservation stage, the nitrogen flow rate is 25~35 L / min, the flow velocity is 0.1~0.2 m / s, and the pressure is 0.08~0.1 MPa; (3) During the cooling stage, the nitrogen flow rate is 65~75 L / min, the flow velocity is 0.8~0.9 m / s, and the pressure is 0.1~0.12 MPa.

[0015] In the above technical solution, the optimal heat treatment environment for aluminum nitride substrate is provided through the coordinated regulation of three stages, which can further reduce the cracking rate of the substrate, while improving the densification degree, thermal conductivity and mechanical strength of the substrate, and greatly improving the consistency and yield of the product.

[0016] In some embodiments, the method further includes the following steps: weighing raw materials, mixing the raw materials with a dispersion medium, binder, plasticizer, and dispersant, and ball milling to prepare a uniform casting slurry; then coating the slurry into a film using a casting machine, and drying it to obtain a green body; finally, heating the green body in an air atmosphere to remove the binder and obtain a pre-sintered green body; the dispersion medium is a mixture of anhydrous ethanol and acetone, with a volume ratio of 3:1; the binder is polyvinyl butyral, added at 2-3 wt% of the total raw material mass; the plasticizer is dibutyl phthalate, added at 50-60 wt% of the binder mass; and the dispersant is triethanolamine, added at 0.3-0.5 wt% of the total raw material mass. In the above technical solution, a mixed solvent of anhydrous ethanol and acetone is selected as the dispersion medium. This utilizes the good wetting properties of ethanol to promote powder dispersion, and the rapid volatility of acetone to optimize the slurry casting characteristics. PVB binder and DBP plasticizer ensure uniform dispersion of organic components and impart sufficient strength and flexibility to the green body, preventing cracks during drying or subsequent processing. Triethanolamine, as a dispersant, prevents the dispersed powder from re-aggregating, ensuring uniform distribution of all powder particles in the slurry. This results in a high-solids content slurry with good leveling and stability, avoiding uneven composition of the green body after casting due to localized particle accumulation. Air-atmosphere debinding treatment thoroughly removes organic components through controlled heating, preventing the rapid volatilization of organic matter from causing pores or internal stress. This ultimately yields a pre-sintered green body with a uniform structure and no agglomeration defects, ensuring high density, high thermal conductivity, and low crack edge / angle ratio of the final substrate.

[0017] In some embodiments, the ball milling time is 12-16 h, the ball-to-material ratio is 6:1, the grinding speed is 350-450 r / min, and the slurry solid content is 60-65 wt%.

[0018] In the above technical solution, sufficient ball milling time ensures that aluminum nitride powder and sintering aids such as Y2O3, ZrO2, and CaF2 are fully refined, avoiding particle agglomeration residue caused by insufficient grinding. A high ball-to-powder ratio of 6:1 provides continuous and uniform grinding intensity, ensuring the uniformity of powder particle size and avoiding the impact of particle size differences caused by insufficient local grinding on the subsequent slurry leveling. A rotation speed of 350~450 r / min balances grinding efficiency and slurry stability, avoiding both excessively low rotation speed leading to a prolonged dispersion cycle and excessively high rotation speed causing a sudden rise in slurry temperature, which could damage the adsorption effect of the dispersant triethanolamine and the structural integrity of the organic binder. A slurry solid content of 60~65 wt% is within the optimal range for tape casting. This solid content ensures that the slurry has good fluidity, meeting the uniform spreading requirements during film coating in the tape casting machine, and also ensures the final density and thermal conductivity of the substrate.

[0019] In some embodiments, the doctor blade gap of the casting machine is 0.3~1.2 mm, the casting speed is 5~8 cm / min; the drying temperature is 60~80 ℃, the drying time is 30~60 min; the green body thickness is 0.25~1.1 mm, and the green body density is ≥2.4 g / cm³. 3 .

[0020] In the above technical solution, by controlling the doctor blade gap within the range of 0.3~1.2 mm and combining it with a casting speed of 5~8 cm / min, the spreading thickness and uniformity of the slurry can be precisely controlled. Simultaneously, by using a drying temperature of 60~80 ℃ and a drying time of 30~60 min, it can be ensured that the ethanol and acetone in the mixed solvent evaporate at a uniform rate without causing cracking or deformation of the green body, ultimately obtaining a thickness of 0.25~1.1 mm and a density ≥2.4 g / cm³. 3 The high density and uniform structure of the green body lays a good foundation for the smooth progress of subsequent debinding and sintering processes, effectively avoiding the problem of cracked edges and corners during sintering caused by defects in the green body structure.

[0021] In some embodiments, the heating rate of the glue removal process is 5~10 ℃ / min, and the temperature is maintained at 600~650 ℃ for 2~3 h. The air flow rate during the glue removal process is 300~500 L / min.

[0022] In the above technical solution, the volume change stress generated during the thermal decomposition of organic components is effectively alleviated by controlling the heating rate of 5~10 ℃ / min. The holding temperature of 600~650 ℃ and the holding time of 2~3 h ensure the full oxidation and decomposition of organic substances such as binders and plasticizers. At the same time, the air flow rate of 300~500 L / min provides sufficient oxygen for the oxidation and decomposition of organic substances and effectively removes pyrolysis products. This allows the adhesive removal process to completely remove organic components without damaging the structure of the green body, thereby obtaining a high-quality pre-sintered green body without cracks or pores, further ensuring the preparation quality of aluminum nitride substrate. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a schematic diagram of a perforated plate airflow sieve structure provided in this application. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0026] Existing aluminum nitride substrates commonly suffer from edge and corner cracking defects during sintering, severely impacting product yield and production efficiency. While current efforts attempt to mitigate this issue through methods such as optimizing powder formulations, improving molding processes, or adjusting sintering temperature profiles, these approaches have significant limitations: formula and process optimizations significantly increase production costs and impose stringent equipment requirements, while simple adjustments to sintering temperature parameters fail to fundamentally resolve the defect problem.

[0027] To address the aforementioned technical problems, this application proposes a method for preparing an aluminum nitride substrate with low edge and crack angle ratios. By using specific component ratios and controlling the nitrogen gas flow rate, velocity, and furnace internal pressure, combined with a perforated airflow sieve inside the furnace, a more stable and uniform sintering environment is provided for the aluminum nitride substrate, thus avoiding edge and crack angle problems caused by thermal stress during sintering. Specifically, the method for preparing an aluminum nitride substrate with low edge and crack angle ratios according to this application includes the following steps: S100. Weigh the following raw materials by mass: 94-97 parts aluminum nitride powder, 1.5-3 parts Y2O3, 0.5-2 parts ZrO2, and 0.1-0.3 parts CaF2.

[0028] This specific raw material ratio establishes a material system that can autonomously regulate the sintering process, absorb internal stress, and optimize the microstructure. Their synergistic effect ensures that the final aluminum nitride substrate can simultaneously achieve the comprehensive performance goals of high density, high thermal conductivity, and low crack edge and crack angle ratio.

[0029] In this step, the aluminum nitride powder has a purity of ≥99.5% and a particle size of 1~5μm, for example, it can be a value within the range of 1μm, 2μm, 3μm, 4μm, 5μm, or any two of these. When the particle size of the aluminum nitride powder meets the above range, it can provide a high specific surface area and sintering driving force, ensuring sufficient densification can be achieved in the subsequent sintering process, thereby enabling the prepared aluminum nitride substrate to obtain high density and high thermal conductivity.

[0030] S200: Mix the raw materials with the dispersion medium, binder, plasticizer and dispersant and ball mill to prepare a uniform cast slurry.

[0031] The dispersion medium is a mixture of anhydrous ethanol and acetone in a volume ratio of 3:1. The good wettability of ethanol allows it to quickly penetrate and coat the surface of the powder particles, while the high volatility of acetone optimizes the casting characteristics of the slurry. The dispersant is triethanolamine, added at 0.3~0.5 wt% of the total raw material mass. The dispersant can adsorb onto the surface of the powder particles, preventing the dispersed powder from re-aggregating and ensuring that all powder particles in the slurry are evenly distributed. The binder is PVB, added at 2~3 wt% of the total raw material mass. The plasticizer is DBP, added at 50~60 wt% of the binder mass. The binder and plasticizer ensure that the green body has both sufficient strength and excellent flexibility, effectively avoiding processing cracks caused by brittle fracture or insufficient plasticity.

[0032] Specifically, in this step, during mixing, the raw material powder and dispersant are first added to the dispersion medium and premixed at low speed for 6-12 hours to ensure that the powder particles are fully wetted by the dispersion medium. At the same time, the dispersant has enough time to migrate and firmly adsorb onto the surface of each powder particle, forming an effective steric hindrance or electrostatic stabilization effect to prevent powder agglomeration. Then, the binder and plasticizer are added to prevent the large molecules of the binder from prematurely encapsulating the powder particles and hindering the effective adsorption of the dispersant, thus ensuring uniform dispersion of the organic components.

[0033] In some embodiments of this application, alumina balls are used as the grinding medium during ball milling, with a ball-to-material ratio of 6:1. The ball milling time is 12-16 hours, for example, values ​​within the range of 12, 13, 14, 15, 16 hours, or any combination thereof. When the ball milling time meets the above range, it ensures that the aluminum nitride powder and various sintering aid particles are sufficiently refined, and that different components achieve uniform mixing at the molecular level, thereby avoiding stress concentration caused by localized uneven composition or residual agglomerates during subsequent sintering. Furthermore, in some embodiments of this application, the grinding speed is 350-450 r / min, for example, values ​​within the range of 350 r / min, 360 r / min, 370 r / min, 380 r / min, 390 r / min, 400 r / min, 410 r / min, 420 r / min, 430 r / min, 440 r / min, 450 r / min, or any combination thereof. When the grinding speed meets the above range, it can provide sufficient kinetic energy to the grinding media, enabling it to generate appropriate impact and shear forces. This effectively breaks up powder agglomerates and promotes uniform mixing of the components, resulting in a homogeneous, agglomerated cast slurry. Too low a grinding speed may lead to insufficient grinding and uneven mixing. Too high a speed may cause rapid heating of the slurry, potentially deteriorating its properties.

[0034] In some embodiments of this application, after the ball milling process is completed, in order to remove the powder agglomerates that were not fully dispersed during the ball milling process, the slurry is filtered through a 200-mesh filter and then allowed to stand for degassing for 2-3 hours to ensure that the slurry has excellent leveling properties and is free of bubbles, so that it meets the molding requirements.

[0035] S300: The slurry is coated into a film using a casting machine and dried to obtain a green body.

[0036] In some embodiments of this application, the blade gap of the casting machine is set to 0.3~1.2 mm according to the target green body thickness. For example, it can be a value within the range of 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, or any two of these values. When the blade gap meets the above range, the spreading thickness of the slurry on the substrate can be precisely controlled, resulting in a green body with uniform thickness and a smooth surface. In addition, in some embodiments of this application, the casting speed of the casting machine is 5~8 cm / min. For example, it can be a value within the range of 5 cm / min, 6 cm / min, 7 cm / min, 8 cm / min, or any two of these values. When the casting speed meets the above range, it can form an optimal match with the set blade gap, ensuring that the slurry has good leveling properties under shear force, while giving the slurry sufficient time to complete spreading and self-leveling on the substrate, thereby obtaining a green body with consistent surface quality and no flow marks.

[0037] In some embodiments of this application, the temperature of the front section of the drying channel is 60 °C and the temperature of the rear section is 80 °C, with a total drying time of 30-60 min. For example, it can be a value within the range of 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, or any combination thereof. When the drying time meets the above range, it ensures that both ethanol and acetone have sufficient time to complete the evaporation process, allowing the green body to reach suitable strength and toughness for subsequent peeling, while avoiding excessively long drying times that would reduce production efficiency.

[0038] In this step, after drying, the green body is peeled off and cut to the target size, resulting in a green body thickness of 0.25~1.1 mm and a green body density ≥2.4 g / cm³. 3 The surface is free of defects such as bubbles, cracks, and missing material.

[0039] S400: The green body is heated and debinded in air to form a pre-sintered green body.

[0040] In some embodiments of this application, the heating rate of the debinding process is 5~10 °C / min, for example, it can be a value within the range of 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, 10 °C / min, or any two of these ranges. When the heating rate of the debinding process meets the above range, it can ensure that the organic components in the green body undergo stable and orderly thermal decomposition, avoiding excessive internal pressure caused by the rapid decomposition and vaporization of organic matter in a short period of time due to excessive heating, thereby effectively preventing microcracks or macroscopic cracking of the green body due to internal stress concentration.

[0041] In some embodiments of this application, the debinding process is heated to 600-650°C, for example, values ​​within the range of 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, or any combination thereof. When the debinding process temperature meets the above range, it can ensure that all kinds of organic components can be completely pyrolyzed into small molecule gases such as CO2 and H2O and discharged.

[0042] In some embodiments of this application, the holding time is 2 to 3 hours, for example, it can be a value within the range of 2 hours, 2.5 hours, 3 hours, or any two of these. When the holding time of the debinding process meets the above range, sufficient time is provided for the complete decomposition of organic matter and the complete diffusion and discharge of gaseous products, thereby obtaining a pure and pollution-free pre-sintered green body.

[0043] In some embodiments of this application, the air flow rate introduced during the debinding process is 300-500 L / min, for example, it can be a value within the range of 300 L / min, 350 L / min, 400 L / min, 450 L / min, 500 L / min, or any combination thereof. When the air flow rate introduced during the debinding process meets the above range, sufficient and continuous oxygen can be provided for the oxidative decomposition of organic matter, ensuring that the pyrolysis reaction proceeds completely while rapidly removing the gaseous products generated by pyrolysis from around the green body and inside the debinding furnace.

[0044] S500: Place the pre-sintered green blank in a calcination furnace and obtain an aluminum nitride substrate through sintering and post-treatment. In this step, a graphite furnace is used for calcination. The temperature is raised to 1760-1780℃ at a rate of 3-5℃ / min, and then raised to 1800-1820℃ at a rate of 1-2℃ / min, and held for 4-8 hours. Simultaneously, a perforated plate airflow screen is installed at the furnace inlet. The perforated plate airflow screen is made of high-temperature resistant graphite material, suitable for the graphite furnace sintering environment. The pre-sintered green blank is then subjected to sintering, cooled, and the separating powder is removed. After edge grinding and surface cleaning, an aluminum nitride substrate is obtained.

[0045] In some embodiments of this application, the aperture of the vent holes in the perforated plate airflow sieve is 1 mm to 3 mm, for example, it can be a value within the range of 1 mm, 2 mm, 3 mm, or any two of these. When the aperture of the perforated plate airflow sieve meets the above range, it can disperse the nitrogen gas entering the furnace into a uniformly distributed micro-airflow, while maintaining an appropriate airflow rate, ensuring the consistency of heating of the substrate and the atmosphere during sintering, thereby significantly reducing thermal stress concentration caused by temperature gradients. Too small an aperture will result in excessive airflow resistance, while too large an aperture will result in poor airflow dispersion.

[0046] In some embodiments of this application, the distribution density of the air vents in the perforated plate airflow screen is 20 per 10 cm. 2 ~50 pieces / 10cm 2 It can be 20 pieces / 10cm 2 25 pieces / 10cm 2 30 pieces / 10cm 2 35 pieces / 10cm 2 40 pieces / 10cm 2 45 pieces / 10cm 2 50 pieces / 10cm 2 Or values ​​within the range of any two of these. When the distribution density of the air vents in the perforated plate airflow sieve meets the above range, nitrogen can be evenly distributed across the cross-section of the furnace, effectively eliminating local airflow dead zones, providing a consistent sintering environment for all parts of the substrate, significantly improving the uniformity of grain growth and the density of the structure, and greatly reducing the cracking rate of the substrate while improving the substrate performance indicators.

[0047] In some embodiments of this application, during the sintering heating stage, the nitrogen flow rate is 30-50 L / min, preferably 35-45 L / min. For example, it can be a value within the range of 30 L / min, 35 L / min, 40 L / min, 45 L / min, 50 L / min, 55 L / min, 60 L / min, or any combination thereof. When the nitrogen flow rate meets the above range during the sintering heating stage, it can quickly replace the air in the furnace, creating a pure inert protective atmosphere in a short time to prevent the aluminum nitride powder and additives from being oxidized. Furthermore, by using a moderate airflow intensity in conjunction with a perforated plate airflow sieve, it can achieve a uniform temperature distribution within the furnace, preventing uneven heating of the substrate due to excessive local airflow and suppressing the generation of thermal stress from the source.

[0048] In some embodiments of this application, during the sintering heating stage, the nitrogen flow rate is 0.5~0.8 m / s, preferably 0.6~0.8 m / s, for example, it can be a value within the range of 0.5 m / s, 0.6 m / s, 0.7 m / s, 0.8 m / s, or any two of these. When the nitrogen flow rate meets the above range during the sintering heating stage, it can balance the air replacement efficiency and airflow stability, which can quickly remove residual oxygen in the furnace without impacting the surface of the green blank due to excessive flow rate. At the same time, it works in conjunction with the flow equalization effect of the perforated plate airflow screen to ensure that the nitrogen gas flows uniformly across the substrate in a laminar flow state, ensuring that all parts of the substrate heat up synchronously and avoiding stress concentration caused by local temperature differences.

[0049] In some embodiments of this application, during the sintering heating stage, the pressure is 0.03~0.1 MPa, preferably 0.05~0.08 MPa. For example, it can be a value within the range of 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa, 0.1 MPa, or any two of these ranges. When the pressure meets the above range during the sintering heating stage, it can maintain the stability of the inert atmosphere in the furnace, prevent the infiltration of outside air, and provide a suitable pressure environment for the uniform diffusion of nitrogen. This also assists the airflow sieve in achieving uniform distribution of nitrogen flow and avoids airflow disturbance caused by excessively high pressure or incomplete atmosphere replacement caused by excessively low pressure.

[0050] In some embodiments of this application, during the sintering holding stage, the nitrogen flow rate is 20-40 L / min, preferably 25-35 L / min. For example, it can be a value within the range of 20 L / min, 22 L / min, 25 L / min, 30 L / min, 35 L / min, 40 L / min, or any combination thereof. When the nitrogen flow rate meets the above range during the sintering holding stage, it can provide a stable inert environment for the liquid phase sintering of the composite sintering aid, avoiding the influence of atmosphere fluctuations on grain growth and densification. It can also carry away trace impurity gases generated during sintering through a gentle airflow, ensuring sufficient sintering and structural stability.

[0051] In some embodiments of this application, during the sintering and holding stage, the nitrogen flow rate is 0.1~0.3 m / s, preferably 0.1~0.2 m / s, for example, it can be a value within the range of 0.1 m / s, 0.2 m / s, 0.3 m / s, or any two of these. When the nitrogen flow rate meets the above range during the sintering and holding stage, the interference of the gas flow on the sintering process can be minimized, the uniformity of temperature and atmosphere in the furnace can be maintained, the full diffusion and bonding of aluminum nitride particles can be promoted, the microstructure of the substrate can be optimized, and the density and mechanical properties can be improved.

[0052] In some embodiments of this application, during the sintering holding stage, the pressure is 0.08~0.1 MPa, for example, it can be a value within the range of 0.08 MPa, 0.09 MPa, 0.1 MPa, or any two of them. When the pressure meets the above range during the sintering holding stage, it can stabilize the sintering environment in the furnace, while suppressing the residue of impurity gases in the billet, avoiding the formation of porosity defects, and laying a good foundation for stress control in the subsequent cooling stage.

[0053] In some embodiments of this application, during the sintering cooling stage, the nitrogen flow rate is 60-80 L / min, preferably 65-75 L / min. For example, it can be a value within the range of 60 L / min, 62 L / min, 65 L / min, 70 L / min, 75 L / min, 80 L / min, or any combination thereof. When the nitrogen flow rate meets the above range during the sintering cooling stage, it can quickly remove a large amount of heat from the furnace, reduce the accumulation of thermal stress generated during the cooling process, and at the same time, in conjunction with the uniform flow effect of the airflow screen, ensure that all parts of the substrate cool synchronously, avoiding edge and corner cracks caused by excessively rapid local cooling.

[0054] In some embodiments of this application, during the sintering cooling stage, the nitrogen flow rate is 0.8~1.0 m / s, preferably 0.8~0.9 m / s, for example, it can be a value within the range of 0.8 m / s, 0.9 m / s, 1.0 m / s, or any two of these. When the nitrogen flow rate meets the above range during the sintering cooling stage, it can ensure rapid heat dissipation while maintaining the stability of the airflow, allowing the substrate to cool at a uniform rate and reducing the risk of thermal stress concentration.

[0055] In some embodiments of this application, during the sintering cooling stage, the pressure is 0.1~0.15 MPa, preferably 0.1~0.12 MPa. For example, it can be a value within the range of 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, 0.15 MPa, or any two of these ranges. When the pressure meets the above range during the sintering cooling stage, it can maintain the sealing of the inert atmosphere in the furnace, prevent outside air from entering and causing oxidation of the substrate during cooling, and at the same time assist in the uniform diffusion of airflow, improve the uniformity of heat dissipation, and ultimately significantly reduce the cracking rate of the aluminum nitride substrate, ensuring that the substrate has excellent overall performance.

[0056] The aluminum nitride substrate prepared using the above method has a density ≥3.25 g / cm³. 3 Thermal conductivity ≥170 W / (m With a cracked edge ratio of ≤1.2%, it possesses the characteristics of high thermal conductivity, high density, and low cracked edge ratio, meeting the demand for high-performance aluminum nitride substrates in electronic manufacturing fields such as high-temperature electronic devices and high-power module packaging.

[0057] The present application will be further described in detail below with reference to the embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available products, and the apparatus or equipment used are all purchased from conventional commercial sales channels. In the specific embodiments of this application, the calcining furnace is a graphite furnace.

[0058] Example 1 The method for preparing the aluminum nitride substrate with low crack angle in this embodiment includes the following steps: (1) Raw material preparation: Weigh 96 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 3μm, 2.5 parts of Y2O3 sintering aid, 1.5 parts of ZrO2 sintering aid, and 0.2 parts of CaF2 sintering aid.

[0059] (2) Slurry preparation: The raw material powder and triethanolamine were added sequentially to a mixed solution of anhydrous ethanol and acetone in a volume ratio of 3:1. The mixture was premixed at low speed for 12 h, and then polyvinyl butyral (PVB) and dibutyl phthalate (DBP) were added. Alumina balls were used as the grinding medium with a ball-to-material ratio of 6:1, a grinding speed of 450 r / min, and a ball milling time of 16 h to obtain a uniform, non-agglomerated cast slurry. After the slurry was ball-milled, it was filtered through a 200-mesh filter and then allowed to stand for 2 h to remove bubbles.

[0060] The proportions of PVB, DBP, and triethanolamine were as follows: PVB was added at 3 wt% of the total raw material mass; DBP was added at 55 wt% of the PVB mass; and triethanolamine was added at 0.4 wt% of the total raw material mass. (3) Casting: The slurry is coated into a film using a casting machine, dried, and then the green body is peeled off and cut to the target size. The resulting green body has a thickness of 0.58 mm and a density ≥ 2.4 g / cm³. 3 .

[0061] The casting machine has a scraper gap of 0.6 mm and a casting speed of 8 cm / min; the temperature of the front section of the drying channel is 60℃ and the temperature of the rear section is 80℃, and the total drying time is 45 min.

[0062] (4) Debinding treatment: The cut green body is laid flat on the boron nitride firing plate, the firing plate is placed in the debinding furnace, and the temperature is raised to 630°C at a rate of 7°C / min. During the heating process, air is introduced at a rate of 400 L / min, and the temperature is maintained at 630°C for 3 h.

[0063] (5) Sintering and post-treatment: The pre-sintered green blank is placed in a graphite furnace, nitrogen is introduced, and the temperature is raised to 1760°C at a rate of 3°C / min, and then raised to 1800°C at a rate of 2°C / min. The temperature is held for 4 hours, and aluminum nitride substrate is obtained through sintering and post-treatment.

[0064] A perforated plate airflow screen is installed at the air inlet of the graphite furnace. The airflow screen has 2 mm pores and a distribution density of 30 pores / 10 cm. 2 .

[0065] During the heating phase, the nitrogen flow rate was 40 L / min, the flow velocity was 0.7 m / s, and the pressure was maintained at 0.07 MPa. During the heat preservation stage, the nitrogen flow rate was 30 L / min, the flow velocity was 0.2 m / s, and the pressure was maintained at 0.09 MPa. During the cooling phase, the nitrogen flow rate was 70 L / min, the velocity was 0.9 m / s, and the pressure was maintained at 0.13 MPa.

[0066] Example 2 The difference from Example 1 is as follows: In step (5), the pore size of the air sieve is 1 mm, and the distribution density is 20 pores / 10 cm. 2 During the heating phase, the nitrogen flow rate was 30 L / min, the flow velocity was 0.5 m / s, and the pressure was maintained at 0.03 MPa; during the heat preservation phase, the nitrogen flow rate was 20 L / min, the flow velocity was 0.1 m / s, and the pressure was maintained at 0.08 MPa; during the cooling phase, the nitrogen flow rate was 60 L / min, the flow velocity was 0.8 m / s, and the pressure was maintained at 0.1 MPa.

[0067] Example 3 The difference from Example 1 is as follows: In step (5), the pore size of the air sieve is 3 mm, and the distribution density is 50 pores / 10 cm. 2 During the heating phase, the nitrogen flow rate was 50 L / min, the flow rate was 0.8 m / s, and the pressure was maintained at 0.1 MPa. During the heat preservation phase, the nitrogen flow rate was 40 L / min, the flow rate was 0.3 m / s, and the pressure was maintained at 0.1 MPa. During the cooling phase, the nitrogen flow rate was 80 L / min, the flow rate was 1.0 m / s, and the pressure was maintained at 0.15 MPa.

[0068] Example 4 The difference from Example 1 is as follows: In step (5), during the heating stage, the nitrogen flow rate is 35 L / min, the flow velocity is 0.6 m / s, and the pressure is maintained at 0.05 MPa; during the heat preservation stage, the nitrogen flow rate is 25 L / min, the flow velocity is 0.1 m / s, and the pressure is maintained at 0.08 MPa; during the cooling stage, the nitrogen flow rate is 65 L / min, the flow velocity is 0.8 m / s, and the pressure is maintained at 0.1 MPa.

[0069] Example 5 The difference from Example 1 is as follows: In step (5), during the heating stage, the nitrogen flow rate is 45 L / min, the flow velocity is 0.8 m / s, and the pressure is maintained at 0.08 MPa; during the heat preservation stage, the nitrogen flow rate is 35 L / min, the flow velocity is 0.2 m / s, and the pressure is maintained at 0.1 MPa; during the cooling stage, the nitrogen flow rate is 75 L / min, the flow velocity is 0.9 m / s, and the pressure is maintained at 0.12 MPa.

[0070] Example 6 The difference from Example 1 is as follows: In step (1), weigh 94 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 1μm, 1.5 parts of Y2O3 sintering aid, 0.5 parts of ZrO2 sintering aid, and 0.1 parts of CaF2 sintering aid.

[0071] Example 7 The difference from Example 1 is as follows: In step (1), weigh out 97 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 5μm, 3 parts of Y2O3 sintering aid, 2 parts of ZrO2 sintering aid, and 0.3 parts of CaF2 sintering aid.

[0072] Example 8 The difference from Example 1 is as follows: In step (1), weigh 95 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 2μm, 2 parts of Y2O3 sintering aid, 1 part of ZrO2 sintering aid, and 0.2 parts of CaF2 sintering aid.

[0073] Example 9 The difference from Example 1 is as follows: In step (1), weigh 96 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 4μm, 3 parts of Y2O3 sintering aid, 2 parts of ZrO2 sintering aid, and 0.3 parts of CaF2 sintering aid.

[0074] Comparative Example 1 The difference from Example 1 is as follows: In step (1), weigh 90 parts of aluminum nitride powder with a purity ≥99.5% and a particle size of 7μm, 6 parts of Y2O3 sintering aid, 3.5 parts of ZrO2 sintering aid, and 0.5 parts of CaF2 sintering aid.

[0075] Comparative Example 2 The difference from Example 1 is as follows: In step (5), the pre-sintered green blank is placed in a graphite furnace without nitrogen gas.

[0076] Comparative Example 3 The difference from Example 1 is as follows: In step (5), during the cooling stage, nitrogen gas is not introduced, allowing it to cool naturally.

[0077] Comparative Example 4 The difference from Example 1 is as follows: In step (5), no airflow screen is installed at the air inlet of the graphite furnace.

[0078] Comparative Example 5 The difference from Example 1 is as follows: In step (5), the pore size of the air sieve is 5 mm, and the distribution density is 10 pores / 10 cm. 2 .

[0079] Performance testing The thermal conductivity, mechanical properties, and density of the aluminum nitride substrates in Examples 1-9 and Comparative Examples 1-5 were tested using a thermal conductivity meter, a universal testing machine, and a density meter, respectively. The cracking of the aluminum nitride substrates at the edges and corners was observed using a scanning electron microscope. The test results are shown in Table 1.

[0080] Table 1 Test results for each embodiment and comparative example

[0081] By comparing Examples 1-9 and Comparative Examples 1-5, it can be seen that the aluminum nitride substrate prepared by the method of this application has the characteristics of high thermal conductivity, high density and low crack edge and crack angle ratio.

[0082] A comparison of Example 1 and Comparative Example 1 shows that aluminum nitride powder, as a matrix material, combined with a specific ratio of Y2O3, ZrO2 and CaF2 composite sintering aids, can enable the components to produce a synergistic effect during the sintering process. The formulation design of this application enables the substrate to obtain high density and high thermal conductivity while effectively releasing internal stress, ultimately significantly reducing the cracking rate of the substrate.

[0083] A comparison of Example 1 with Comparative Examples 2 and 3 shows that maintaining and controlling the nitrogen flow rate, velocity, and pressure in stages throughout the sintering process is crucial for promoting uniform sintering of the aluminum nitride substrate. This results in the final aluminum nitride substrate achieving excellent density and thermal conductivity while significantly reducing the cracking rate of the aluminum nitride substrate.

[0084] By comparing Example 1 with Comparative Examples 4 and 5, it can be seen that the porous plate airflow sieve can make the nitrogen atmosphere evenly distributed in the furnace, improve the uniformity and consistency of substrate sintering, and reduce the risk of edge and corner cracking during the sintering process.

[0085] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. An aluminum nitride substrate with low crack angle ratio, characterized in that, The composition of the substrate, by mass, includes: 94-97 parts aluminum nitride powder, 1.5-3 parts Y2O3, 0.5-2 parts ZrO2, and 0.1-0.3 parts CaF2; The aluminum nitride powder has a purity of ≥99.5% and a particle size of 1~5μm; A method for preparing an aluminum nitride substrate with low crack angle ratio includes the following steps: Weigh the following raw materials by weight: 94-97 parts aluminum nitride powder, 1.5-3 parts Y2O3, 0.5-2 parts ZrO2, and 0.1-0.3 parts CaF2, and process them into pre-sintered green blanks. The pre-sintered green blank is placed in a calcining furnace, and aluminum nitride substrate is obtained through sintering process and post-treatment. An airflow screen is provided at the air inlet of the furnace chamber of the calcining furnace; nitrogen gas is introduced into the furnace chamber through the airflow screen. The sintering process includes a heating stage, a holding stage, and a cooling stage; During the heating phase, the nitrogen flow rate is 30~50 L / min, the flow velocity is 0.5~0.8 m / s, and the pressure is 0.03~0.1 MPa; During the heat preservation stage, the nitrogen flow rate is 20~40 L / min, the flow velocity is 0.1~0.3 m / s, and the pressure is 0.08~0.1 MPa; During the cooling phase, the nitrogen flow rate is 60~80 L / min, the flow velocity is 0.8~1.0 m / s, and the pressure is 0.1~0.15 MPa; The airflow screen is a perforated plate airflow screen, and the perforated plate airflow screen is provided with air vents, which meet the following conditions: (1) The diameter of the vent hole is 1 mm to 3 mm; (2) The distribution density of the vent holes is 20 per 10 cm. 2 ~50 pieces / 10cm 2 .

2. The aluminum nitride substrate according to claim 1, characterized in that, The substrate comprises, by mass, 95-97 parts of aluminum nitride powder, 2-3 parts of Y2O3, 1-2 parts of ZrO2, and 0.2-0.3 parts of CaF2.

3. The aluminum nitride substrate according to claim 1, characterized in that, The aluminum nitride substrate satisfies at least one of the following conditions: (1) Density ≥ 3.25 g / cm³ 3 ; (2) Thermal conductivity ≥ 170 W / (m K); (3) The cracking ratio of the edge and the cracking angle is ≤1.2%.

4. A method for preparing an aluminum nitride substrate with low crack angle ratio, characterized in that, Includes the following steps: Weigh the following raw materials by weight: 94-97 parts aluminum nitride powder, 1.5-3 parts Y2O3, 0.5-2 parts ZrO2, and 0.1-0.3 parts CaF2, and process them into pre-sintered green blanks. The pre-sintered green blank is placed in a calcining furnace, and aluminum nitride substrate is obtained through sintering process and post-treatment. An airflow screen is provided at the air inlet of the furnace chamber of the calcining furnace; nitrogen gas is introduced into the furnace chamber through the airflow screen. The sintering process includes a heating stage, a holding stage, and a cooling stage; During the heating phase, the nitrogen flow rate is 30~50 L / min, the flow velocity is 0.5~0.8 m / s, and the pressure is 0.03~0.1 MPa; During the heat preservation stage, the nitrogen flow rate is 20~40 L / min, the flow velocity is 0.1~0.3 m / s, and the pressure is 0.08~0.1 MPa; During the cooling phase, the nitrogen flow rate is 60~80 L / min, the flow velocity is 0.8~1.0 m / s, and the pressure is 0.1~0.15 MPa; The airflow screen is a perforated plate airflow screen, and the perforated plate airflow screen is provided with air vents, which meet the following conditions: (1) The diameter of the vent hole is 1 mm to 3 mm; (2) The distribution density of the vent holes is 20 per 10 cm. 2 ~50 pieces / 10cm 2 .

5. The preparation method according to claim 4, characterized in that, The sintering process satisfies at least one of the following conditions: (1) During the heating stage, the nitrogen flow rate is 35~45 L / min, the flow velocity is 0.6~0.8 m / s, and the pressure is 0.05~0.08 MPa; (2) During the heat preservation stage, the nitrogen flow rate is 25~35 L / min, the flow velocity is 0.1~0.2 m / s, and the pressure is 0.08~0.1 MPa; (3) During the cooling stage, the nitrogen flow rate is 65~75 L / min, the flow velocity is 0.8~0.9 m / s, and the pressure is 0.1~0.12 MPa.

6. The preparation method according to claim 4, characterized in that, The process also includes the following steps: weighing the raw materials, mixing the raw materials with a dispersion medium, binder, plasticizer, and dispersant, and ball milling to prepare a uniform casting slurry; then coating the slurry into a film using a casting machine, and drying it to obtain a green body; finally, heating the green body in an air atmosphere to remove the binder and obtain a pre-sintered green body. The dispersion medium is a mixture of anhydrous ethanol and acetone in a volume ratio of 3:

1. The binder is polyvinyl butyral, and the amount added is 2-3 wt% of the total mass of the raw materials. The plasticizer is dibutyl phthalate, and the amount added is 50-60 wt% of the adhesive. The dispersant is triethanolamine, and the amount added is 0.3~0.5 wt% of the total mass of the raw materials.

7. The preparation method according to claim 6, characterized in that, The ball milling process takes 12-16 hours, the ball-to-material ratio is 6:1, and the grinding speed is 350-450 r / min. The slurry has a solid content of 60-65 wt%.

8. The preparation method according to claim 6, characterized in that, The blade gap of the casting machine is 0.3~1.2 mm, and the casting speed is 5~8 cm / min; The drying process is carried out at a temperature of 60-80 ℃ for a time of 30-60 min. The green body thickness is 0.25~1.1 mm, and the green body density is ≥2.4 g / cm³. 3 .

9. The preparation method according to claim 6, characterized in that, The heating rate of the glue removal process is 5~10 ℃ / min, and the temperature is maintained at 600~650 ℃ for 2~3 h. The air flow rate during the glue removal process is 300~500 L / min.

Citation Information

Patent Citations

  • Slurry of high-performance aluminum nitride ceramic substrate and preparation method thereof

    CN112374896A

  • Preparation method of aluminum nitride ceramic substrate sintered by graphite furnace

    CN112898028A